Uptake, Retention, and Adherence to Pre-exposure Prophylaxis (PrEP) in TRIUMPH: A Peer-Led PrEP Demonstration Project for Transgender Communities in Oakland and Sacramento, California. (15th December 2021) - Sevelius, Jae M.; Glidden, David V.; Deutsch, Madeline; Welborn, Layla; Contreras, Alejandro; Salinas, Arianna; Venegas, Luz; Grant, Robert M.
Abstract : Background: TRIUMPH (Trans Research–Informed communities United in Mobilization for the Prevention of HIV) was a community-led, transgender-specific pre-exposure prophylaxis (PrEP) demonstration project at 2 community-based clinical sites in California. TRIUMPH used peer health education, community mobilization, and clinical integration of PrEP with hormone therapy to promote PrEP knowledge and acceptability. The goal of this study was to evaluate PrEP uptake, retention, and adherence among TRIUMPH participants and examine site-based differences. Methods: Eligible participants were adult transgender and gender diverse people interested in PrEP. Participants were seen at baseline and at 1, 3, 6, 9, and 12 months for PrEP provision, clinical visits, and HIV testing. PrEP uptake was defined as dispensation of PrEP, PrEP retention was defined as proportion of expected visits completed among those who initiated PrEP, and PrEP adherence was assessed by measuring tenofovir diphosphate concentrations in dried blood spots. Logistic regression models quantified the association of variables with PrEP outcomes. Results: TRIUMPH enrolled 185 participants; the median age was 28 years (interquartile range: 23–35), 7% was Black, and 58% was Latinx. PrEP uptake was as follows: 78% in Oakland and 98% in Sacramento; 91% among trans women, 96% among trans men, and 70% among nonbinary participants. Almost half (47%) rarely/never believed about HIV, and 42% reported condomless sex act in the past 3 months. Participants who reported higher numbers of sex partners were more likely to be retained and adherent; other predictors of adherence included not having a primary partner and not experiencing violence in the past 3 months. Conclusions: This community-led, trans-specific PrEP demonstration project documents high levels of PrEP initiation in a young transgender and gender diverse cohort at risk of HIV acquisition.